Strength and conditioning roundtable: Strength and conditioning coach evaluation - Gillham, A.; Doscher, M.; Fitzgerald, C.; Bennett, S.; Davis, A.; Banwarth, A. (International Journal of Sports Science & Coaching, 2017)
Evaluation is a necessary component of nearly every job and strength and conditioning coaches are no exception. However, the utility of that evaluation seems likely to vary tremendously across the sporting landscape. The literature is lacking information on how strength and conditioning coaches are evaluated. Therefore, the purpose of this project was to solicit responses from head strength and conditioning coaches regarding their experiences with evaluation of their work. Five coaches representing competitive levels from high school to professional American football responded to a series of 11 questions about evaluations and assessments. Their answers were more diverse than similar and combined to present a picture of evaluation that is entirely inconsistent and muddled. ABSTRACT FROM AUTHOR